1986
DOI: 10.1128/iai.54.2.328-332.1986
|View full text |Cite
|
Sign up to set email alerts
|

Localization of binding sites for purified Escherichia coli P fimbriae in the human kidney

Abstract: Binding sites in the human kidney for purified P fimbriae of pyelonephritogenic Eschenichia coli were determined. The purified KS71A (F71) fimbriae bound only to epithelial elements of the kidney, i.e., to the apical aspect of proximal and distal tubular cells, as well as to the apical and cytoplasmic sites of collecting ducts. In addition, binding was seen at the vascular endothelium throughout the kidney and at the parietal epithelium of the glomeruli. The binding was specifically inhibited by the receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Similarly, none of the bacterial mutants analysed displayed significantly lower than normal levels of internalization, suggesting that the mechanism of entry of AL511 into CD cells differs from that of the UPEC UTI89 and NU14 strains in bladder cells, in which type 1 adhesins have been shown to play a central role. P fimbriae, which are produced by most pyelonephritis isolates (Bergsten et al ., 2005) and recognize receptors located on the luminal surface of renal tubules (Korhonen et al ., 1986; Connell et al ., 2000), do not seem to be involved in the uptake of AL511 into renal epithelial cells. UPEC strains expressing Afa adhesins also display a unique renal tissue tropism (Nowicki et al ., 1988; Lalioui and Le Bouguénec, 2001; Le Bouguénec, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, none of the bacterial mutants analysed displayed significantly lower than normal levels of internalization, suggesting that the mechanism of entry of AL511 into CD cells differs from that of the UPEC UTI89 and NU14 strains in bladder cells, in which type 1 adhesins have been shown to play a central role. P fimbriae, which are produced by most pyelonephritis isolates (Bergsten et al ., 2005) and recognize receptors located on the luminal surface of renal tubules (Korhonen et al ., 1986; Connell et al ., 2000), do not seem to be involved in the uptake of AL511 into renal epithelial cells. UPEC strains expressing Afa adhesins also display a unique renal tissue tropism (Nowicki et al ., 1988; Lalioui and Le Bouguénec, 2001; Le Bouguénec, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm the accessibility of specific binding sites for S fimbriae on living human endothelial cells. In contrast, the binding of P fimbriae to the cultured endothelial cells was unexpectedly low compared with their intense binding to vascular endothelium in kidney sections (10). This might be due to the inability of the immunohistochemical method to detect quantitative differences in the binding of different fimbriae, but it may also suggest that the binding sites observed in the immunohistochemical study are poorly accessible for P fimbriae on intact endothelial cells.…”
mentioning
confidence: 80%
“…4). Earlier immunohistochemical studies employing incubation of purified adhesins with tissue sections have demonstrated intense binding of S fimbriae (8) and P fimbriae (10) to vascular endothelium in human kidney. In similar experiments, no binding of type 1 fimbriae to human vascular endothelium was observed (24).…”
mentioning
confidence: 99%
“…P fimbria is a particularly important adhesin and is expressed by nearly 100% of strains associated with pyelonephritis (395). P-fimbriated E. coli is able to bind the uroepithelium as well as proximal renal tubules, glomerular epithelium, and vascular endothelium (396,397). P fimbriae not only facilitate multivalent bacterial adhesion to uroepithelium but also stimulate the release of inflammatory mediators through ceramide and Toll-like receptor (TLR4) pathways (394,398,399).…”
Section: Uropathogenic E Colimentioning
confidence: 99%